The (Bio) Political Violence in Atwood’s Alias Grace - Sharma, Pradip (Humanities and Social Sciences Journal, 2021)
This research explores the (bio)political violence that sets the subject position and subjugation of the women characters including Grace Marks in Margaret Atwood’s Alias Grace. Grace is acquitted as murderess and sent to jail, and to the lunatic asylum to make her docile and succumb to sovereign power. It is biopolitics, the sovereign power over populations that is deployed via social institutions to make her manageable and go docile. Through the state apparatuses the biopolitical governmentality constitutes and disseminates knowledge that helps Grace formulate her subjectivity and subjects to the law. Being a woman, she is discarded, sexually abused, and retained in bare life in the jail. In particular, her resignation to the power marks the inclusive exclusion and political violence over her. This reflect her perennial exclusion from social life. Finally, her servitude, amnesty and wedding epitomizes her oikos and docility under the (bio)political violence.